2000
DOI: 10.1029/1999ja900463
|View full text |Cite
|
Sign up to set email alerts
|

Electric field variability associated with the Millstone Hill electric field model

Abstract: Abstract. Joule heating that is generated at high latitudes in the thermosphere because of the magnetospherically imposed electric potential •s proportional to the average of the square of the electric field (E field)ø Most theoretical Joule heating computations use only average electric fields, resulting in heating that is proportional to the square of the average E field. The computation of the average of the square of the E field requires knowledge about the statistical characteristics of E field variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
138
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(152 citation statements)
references
References 14 publications
14
138
0
Order By: Relevance
“…At first glance, this might seem a surprising result and inconsistent with the results of Codrescu et al (2000). But we have used a different analysis approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At first glance, this might seem a surprising result and inconsistent with the results of Codrescu et al (2000). But we have used a different analysis approach.…”
Section: Discussionmentioning
confidence: 99%
“…First, we estimate typical variations of electric fields using data collected by the European Incoherent Scatter (EISCAT) radar (Rishbeth and Williams, 1984). The results are compared with those of Codrescu et al (2000). We then use these findings to modify the input parameters to the coupled thermosphere-ionosphere-plasmasphere model known as CTIP to determine both the thermospheric and ionospheric consequences of using a more realistic electric field description.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they found no relationship with magnetic activity, that is, the gravity wave amplitude and occurrence rate did not depend on Kp. However, Codrescu et al (2000) have shown that small-scale electric field fluctuations can lead to Joule heating effects, even at low Kp. Alternatively, the in situ generation of gravity waves discussed by Vadas et al (2003) and Vadas and Liu (2009) may be the source.…”
Section: Introductionmentioning
confidence: 99%